2015
DOI: 10.1126/science.aab4090
|View full text |Cite
|
Sign up to set email alerts
|

ACD toxin–produced actin oligomers poison formin-controlled actin polymerization

Abstract: The actin crosslinking domain (ACD) is an actin-specific toxin produced by several pathogens, including life-threatening spp. of Vibrio cholerae, Vibrio vulnificus, and Aeromonas hydrophila. Actin crosslinking by ACD is thought to lead to slow cytoskeleton failure owing to a gradual sequestration of actin in the form of nonfunctional oligomers. Here we found that ACD converted cytoplasmic actin into highly toxic oligomers that potently "poisoned" the ability of major actin assembly proteins, formins, to sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(91 citation statements)
references
References 46 publications
3
88
0
Order By: Relevance
“…Moreover, only a small fraction of actin modification by ACD appears to be sufficient to induce major cellular effects. The answer to these questions may be the recent finding of the role of cross-linked actin on formin-regulated actin polymerization (Heisler et al 2015) (Fig. 8).…”
Section: Functional Consequences Of Actin Cross-linking By Acdsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, only a small fraction of actin modification by ACD appears to be sufficient to induce major cellular effects. The answer to these questions may be the recent finding of the role of cross-linked actin on formin-regulated actin polymerization (Heisler et al 2015) (Fig. 8).…”
Section: Functional Consequences Of Actin Cross-linking By Acdsmentioning
confidence: 98%
“…For host-pathogen interactions, this means inhibition of migration of immune cells or blockade of phagocytosis. At least in vitro, the rate of actin cross-linking induced by ACD is rather low (Heisler et al 2015). Considering the large pool of actin in cells, the rapid effects of ACD on cell morphology are difficult to explain.…”
Section: Functional Consequences Of Actin Cross-linking By Acdsmentioning
confidence: 99%
“…The toxin is comprised of several well-defined components: i) a variable number (from one to five) of effector domains with distinct toxicities found in different combinations; ii) a cysteine protease domain (CPD) always positioned C-terminally to the effector domains and responsible for domain liberation upon delivery into a host cell (Prochazkova et al, 2009; Shen et al, 2009); and iii) the N- and C-terminal glycine-rich Ca 2+ -binding repeats that serve for membrane integration and translocation across the membrane (Kim et al, 2015). The specific enzymatic activity of one of the MARTX effector domains, actin cross-linking domain (ACD; (Heisler et al, 2015; Kudryashova et al, 2016a)) produced by V. cholerae and A. hydrophila , was tested in vitro and found to be potently inhibited by α- (HNP1, HD5; (Kudryashova et al, 2014b)) and θ-defensins (RC1 and RC101; (Kudryashova et al, 2015)). Cytotoxicity of both ACD and Rho inhibitory effector domain (RID; (Ahrens et al, 2013)) was prevented by HNP1 in cell culture experiments (Kudryashova et al, 2014b).…”
Section: Defensin-susceptible Bacterial Toxins/effector Proteinsmentioning
confidence: 99%
“…Exciting new studies suggest that actin can be converted into a second messenger that amplifies low abundant toxin function (Heisler et al 2015). The actin cross-linking domain (ACD) found in toxins such as the multifunctional autoprocessing repeats-in-toxin (MARTX)-containing toxins covalently cross-links actin into oligomers that are structurally incompatible for polymerization, resulting in rapid cell rounding with loss of all polymerized actin (Fullner & Mekalanos 2000, Lin et al 1999).…”
Section: Figurementioning
confidence: 99%
“…It was previously thought that ACD toxicity was a consequence of cross-linking the G-actin pool into polymerization-deficient oligomers (Cordero et al 2006, Fullner & Mekalanos 2000, Lin et al 1999). However, due to the inconsistencies between in vitro ACD activity (which is low) and cell G-actin concentrations (which are high), Heisler et al (2015) proposed that toxicity is caused by ACD cross-linked actin oligomers targeting upstream actin regulator proteins. Indeed, they found that actin oligomers poison the formin family of actin nucleators.…”
Section: Figurementioning
confidence: 99%